DFT insights into the stoichiometric (001), (011) and (111) thin film surfaces of Ba2NaIO6 - Alqorashi, Afaf Khadr; Almalki, Wafa Mohammed; Ullah, Sami; Algethami, Norah; Khan, Firoz; Laref, Amel (Solid state communications, 2024)
In this work, first-principles DFT calculations were performed to investigate the geometric, electronic, and magnetic properties of double perovskite Ba2NaIO6 (BNIO) in the bulk, and thin film form. The results showed that bulk BNIO in cubic phase (Fm-3m, #225) has a lattice constant of 8.43 Å, and is a non-magnetic direct band gap (Eg) semiconductor with Eg of 2.22 eV. Three types of cleaved surfaces namely (001), (011), and (111) oriented surfaces were considered here. The stability of the surfaces was examined with surface energy (Es). The Es is found to be 0.06, 0.09, 0.14 eV/Å2 respectively, for (001), (011), and (111) surface, indicating (001) as the energetically most favorable surface. All three surfaces exhibited metallic character, dominated by the splitting of O-p states of the top layer O-atoms. The (001) and (111) surfaces exhibited a magnetic character with magnetic moments of 0.1 and 2.23 μB per formula unit, whereas the (011) surface remained non-magnetic. •DFT calculations were used to study the electronic properties of Ba2NaIO6 in bulk and thin film..•The (001) surface was found more stable than (011), and (111) surface.•All the selected surfaces exhibited metallic characteristics.•The (001) and (111) surfaces exhibited a magnetic character, whereas (011) remained non-magnetic.